Sustainable Development of Rural Areas. Assessment of the Investment Appeal of the Region - KALDIYAROV, Daniyar; KASENOVA, Aibarshyn; DYRKA, Stefan; BISKUPSKI, Roman; BEDELBAYEVA, Assel (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021DO - 10.14505/jemt.v12.1(49).05, 2021)
The article is devoted to the problem of sustainable development of rural areas as part of the investment policy. The investment appeal of the rural areas in Kazakhstan has been analyzed in the study, and the existing methods for assessing the investment appeal of the rural areas from the standpoint of their sustainable development have been considered. The authors focus on the method for assessing the factors contributing to the formation of investment appeal of the rural areas. A factor score of the investment appeal of the rural areas has been determined using a correlation regression analysis, which revealed the ease of use for a potential investor. Based on the assessment and analysis of the investment potential of the rural areas, proposals have been formulated to improve the method for assessing the investment appeal of the rural areas, taking into account a wide range of factors and monitoring the investment climate in the rural areas .